MAKANAN DAN KEBIASAAN MAKAN KEPITING BAKAU (Scylla serrata Forskal 1775) DI PERAIRAN KAMPUNG SENTOSA BARAT KELURAHAN BELAWAN SICANANG KECAMATAN MEDAN BELAWAN - Nur Basani Pasaribu; Darma Bakti; Ani Suryanti (AQUACOASTMARINE, 2018)
One method to find out food and feeding habits of mangrove crabs (Scylla serrata) is to examine what types of foods contained in the stomach of mangrove crab and feeding period of mangrove crab. The purpose of this study are the type of food, to know the time period of feeding crab mangrove and to determine the effect of time on the mangrove crab in the mangrove ecosystem in Kampung Sentosa. Characteristic observed food type, meal time mangrove crab. Analysis of food data and feeding habits method to research data by using the formula FK, E, ISC and IP. The results of data analysis found the type of mangrove crab food in the form of shellfish, shrimp, fish, moss and mangrove leaves. Mangrove crabs are more active to find food at night, especially from 12 am to 12 pm. Periods of mangrove crabs do not depend on time because they can find food anytime.Keywords: Food, Mangrove Crab, Sicanang Belawan, Feeding Habits